2005
DOI: 10.2165/00002018-200528100-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Prescribing Errors in Hospital Inpatients

Abstract: Many different methods have been used to study the incidence of prescribing errors in hospital inpatients. The objectives of this review were to outline the methods used, highlight their strengths and limitations, and summarise the incidence of prescribing errors reported. Methods used may be retrospective or prospective and based on process or on outcome. Reported prescribing error rates vary widely, ranging from 0.3% to 39.1% of medication orders written and from 1% to 100% of hospital admissions. Unfortunat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
4
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 59 publications
1
81
4
7
Order By: Relevance
“…However, the studies used very different definitions, denominators and methods making it impossible to synthesise overall error rates (Franklin et al, 2005). In particular, three studies relied on incident reports (Ito and Yamazumi, 2003;Haw et al, 2006;Maidment and Thorn, 2006), and will be subject to gross under-reporting (Franklin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies used very different definitions, denominators and methods making it impossible to synthesise overall error rates (Franklin et al, 2005). In particular, three studies relied on incident reports (Ito and Yamazumi, 2003;Haw et al, 2006;Maidment and Thorn, 2006), and will be subject to gross under-reporting (Franklin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of an appropriate denominator is essential when presenting prescribing error data [1]. In addition to the number of newly written medication orders, we obtained data on two other measures of activity for each clinical specialty.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Prescribing errors are common and have the potential for serious patient harm [1]. In the UK, hospital pharmacists identify and resolve prescribing errors as part of their routine daily monitoring of all prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it was appropriately powered to identify differences in prescribing error rates, given the relatively rarer occurrence of clinical errors or harm to patients, this study hasn't demonstrated impact on these key outcome measures. Additionally, it must be noted that the error rate calculated for this study were different to many other published studies [25]. These studies measure the number of errors that occur as a proportion of the potential opportunities for error.…”
Section: Discussionmentioning
confidence: 75%